The Critical Role of Host and Bacterial Extracellular Vesicles in Endometriosis - Michaela Wagner; Chloe Hicks; Emad El-Omar; Valery Combes; Fatima El-Assaad (Biomedicines)
Endometriosis is a chronic, inflammatory, oestrogen-dependent disorder that is defined by the presence of endometrium-like tissue in the extra-uterine environment. It is estimated to affect approximately 10% of women of reproductive age, and the cause is still largely unknown. The heterogenous nature and complex pathophysiology of the disease results in diagnostic and therapeutic challenges. This review examines the emerging role of host extracellular vesicles (EVs) in endometriosis development and progression, with a particular focus on bacterial extracellular vesicles (BEVs). EVs are nano-sized membrane-bound particles that can transport bioactive molecules such as nucleic acids, proteins, and lipids, and therefore play an essential role in intercellular communication. Due to their unique cargo composition, EVs can play a dual role, both in the disease pathogenesis and as biomarkers. Both host and bacterial EVs (HEVs and BEVs) have been implicated in endometriosis, by modulating inflammatory responses, angiogenesis, tissue remodelling, and cellular proliferation within the peritoneal microenvironment. Understanding the intricate mechanisms underlying EVs in endometriosis pathophysiology and modulation of the lesion microenvironment may lead to novel diagnostic tools and therapeutic targets. Future research should focus on uncovering the specific cargo, the inter-kingdom cell-to-cell interactions, and the anti-inflammatory and anti-microbial mechanisms of both HEVs and BEVs in endometriosis in the hope of discovering translational findings that could improve the diagnosis and treatment of the disease.